The prepared leader : emerge from any crisis more resilient than before - James, Erika H.; Wooten, Lynn Perry (Wharton School Press, 2022)
"From their unique perch at the top of two most prestigious institutions, Erika H. James and Lynn Perry Wooten provide a roadmap for leaders to help them lead through any crisis. The next crisis might be here now, or it might be around the corner. In The Prepared Leader: Emerge from Any Crisis More Resilient Than Before, two history-making experts in crisis leadership--James, dean of The Wharton School of the University of Pennsylvania, and Wooten, president of Simmons University--forcefully argue that the time to prepare is always. In no other time in recent history have leaders in every industry and on every continent grappled with so many changes that have independently and simultaneously undermined their ability to lead. The Prepared Leader encapsulates more than two decades of the authors' research to convey how it has positioned them to navigate through the distinct challenges of today and tomorrow. Their insights have implications for every leader in every industry and every worker at every level. In their fast-reading and actionable book, James and Wooten provide tools and frameworks for addressing and learning from crises, and they provide insight into what you need to know to become a Prepared Leader, including: The five phases of crisis management and the skills you need for each phase. They examine how the National Basketball Association and its commissioner, Adam Silver, responded to the COVID-19 pandemic. Making the right decisions under pressure and how to avoid common mistakes. They reveal how Burger King CEO Jose Cil began planning for the aftermath of a crisis right in the middle of one. Building a crisis leadership team and how to lead one that you've inherited. They detail how Wonya Lucas, CEO and President of the Crown Media Family Networks, aligned and mobilized an executive team during a time of crisis. James and Wooten argue that--in addition to people, profit, and the planet--prepared leadership should be the fourth "P" in a company's bottom line. They bring decades of world-renowned research on crisis leadership, diversity and inclusion, management strategy, and positive leadership to the table to help leaders better prepare themselves to lead through crises--and for whatever lies around the corner."--